Determinants of the Demand for cervical cancer secondary prevention services in Peru - Sanabria-Montañez, César (2021)
Introduction. The preventive services of health are very important like investment in the health of the people. If the secondary preventive services are examined to face the cervical cancer (CCU) in Peru, its access and demands are not equitable. In this article, the determining factors of the demand of services of Pap smear screening (services PAP) are identified and measured. Methods. One studied to a population of women of 30 to 49 years, with data of the Demographic Survey and of Family Health (ENDES) of years 2016 to 2019. A logistic model was used to explore the relation between demand of services PAP and variables of decision, socioeconomics and of health of the people. The predictability of the model based on the machine learning was examined. Results. The factors with the greatest probability of demand PAP services were having hypertension (OR = 4.76; 95% CI: 4.03 - 5.66) and belonging to the “richest” socioeconomic stratum (OR = 3.39, 95% CI: 2.96 - 3.87). On the contrary, with less probability of demand they were, living in small cities (OR = 0.27; 95% CI: 0.24-0.30), in Villages (OR = 0.26; 95% CI: 0.23-0.30) and in the High Andean Sierra. (OR = 0.46, 95% CI: 0.41-0.51). Conclusions. Structural factors, living conditions and place of residence are the main determinants of the demand for PAP preventive services in Peru, which implies greater efforts in health policy and the need to coordinate with other sectors.